Neoplastic diseases prevalence in a turkish university hospital - (:unkn) unknown (My University, 2003)
PURPOSE: The purpose of this study was to register the different cancer cases diagnosed in our hospital with an aim to define the most common and treatable cancer types and help define accurate targets for the allocation of the already limited resources of the Ministry of Health. MATERIALS AND METHODS: We surveyed 12 months of the hospital's pathology records to determine the prevalence of various cancer types. RESULTS: Out of 9720 biopsy and cytology samples, 662 were cancer cases. Breast and gastric cancers were higher and colorectal cancers were lower than the series reported from the United States. Of the pulmonary malignancies, lung cancer in general was not particularly higher in proportion to other cases, something interesting for a country with smoking rates exceeding 60% of the adult population. Squamous cell lung cancer was more common compared to the rates reported in the western world statistics. CONCLUSION: Although biases may exist, as certain cancers are more amenable to surgical intervention and physician groups may have special interest toward a particular cancer, distribution of cancer cases in Turkey is probably similar to the western world.